2012
DOI: 10.1007/s12272-012-1018-6
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of breast cancer tissues to identify biomarker candidates by gel-assisted digestion and label-free quantification methods using LC-MS/MS

Abstract: This study presents a proteomic method that differentiates between matched normal and breast tumor tissues from ductal carcinoma in situ (DCIS) and invasive carcinoma from Korean women, to identify biomarker candidates and to understand pathogenesis of breast cancer in protein level. Proteins from tissues obtained by biopsy were extracted by RIPA buffer, digested by the gel-assisted method, and analyzed by nano-UPLC-MS/MS. From proteomic analysis based on label-free quantitation strategy, a non-redundant list … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 29 publications
4
28
0
Order By: Relevance
“…Similar findings were reported by other research groups (Bini, et al 1997;Chahed, et al 2005;Kabbage, et al 2013;Song, et al 2012;Zamanian, et al 2016) that also observed high CALR expression in breast cancer samples compared to histologically normal tissues using proteomics analysis. CALR overexpression was also correlated with lymph node metastasis and with postoperative appearance of distant metastases in ERBB2 (Her2/neu) positive breast cancer (Eric, et al 2009).…”
Section: Breast Cancersupporting
confidence: 90%
“…Similar findings were reported by other research groups (Bini, et al 1997;Chahed, et al 2005;Kabbage, et al 2013;Song, et al 2012;Zamanian, et al 2016) that also observed high CALR expression in breast cancer samples compared to histologically normal tissues using proteomics analysis. CALR overexpression was also correlated with lymph node metastasis and with postoperative appearance of distant metastases in ERBB2 (Her2/neu) positive breast cancer (Eric, et al 2009).…”
Section: Breast Cancersupporting
confidence: 90%
“…The most widely accepted ECM extraction protocols involve differential tissue fractionation followed by solubilizing the remaining protein in a strong denaturing buffer; radioimmune precipitation assay buffer (Nonidet P-40, sodium deoxycholate and SDS) (10,29), SDS (23,24), guanidine-hydrochloride (11,25), or urea (21, 26 -28). Our pilot studies using these protocols resulted in relatively similar ECM protein profiles and uniformly yielded a protein-containing pellet after extraction.…”
Section: Resultsmentioning
confidence: 99%
“…Currently accepted and widely used digestion methods require proteins to be solubilized for bottom-up proteomic analysis (22). Recent papers have reported characterization of the ECM fraction from tissues through the use of strong chaotropes (11,21,(23)(24)(25)(26)(27) or cellular fractionation followed by strong detergent (10,28,29). However, in our experience, these protocols invariably yield various sizes of an insoluble protein-containing pellet when applied to a variety of tissue samples (heart, lung, and mammary gland).…”
mentioning
confidence: 99%
“…Song and colleagues [30] published a proteomic comparison between normal and breast cancer tissues. Differentially expressed proteins in tumor tissues were related to glycolysis/gluconeogenesis among other pathways.…”
Section: Discussionmentioning
confidence: 99%